Elevated fibrosis burden as assessed by MRI predicts cryoballoon ablation failure. (30th December 2022) - Boyle, Patrick M.; Sarairah, Sakher; Kwan, Kirsten T.; Scott, Griffin D.; Mohamedali, Farzana; Anderson, Carter A.; Bifulco, Savannah F.; Ordovas, Karen G.; Prutkin, Jordan; Robinson, Melissa; Sridhar, Arun R.; Akoum, Nazem
Abstract: Introduction: Late‐gadolinium enhancement magnetic resonance (LGE‐MRI) imaging is increasingly used in management of atrial fibrillation (AFib) patients. Here, we assess the usefulness of LGE‐MRI‐based fibrosis quantification to predict arrhythmia recurrence in patients undergoing cryoballoon ablation. Our secondary goal was to compare two widely used fibrosis quantification methods. Methods: In 102 AF patients undergoing LGE‐MRI and cryoballoon ablation (mean age 62 years; 64% male; 59% paroxysmal AFib), atrial fibrosis was quantified using the pixel intensity histogram (PIH) and image intensity ratio (IIR) methods. PIH segmentations were completed by a third‐party provider as part of the standard of care at our hospital; Image intensity ratio (IIR) segmentations of the same scans were carried out in our lab using a commercially available software package. Fibrosis burdens and spatial distributions for the two methods were compared. Patients were followed prospectively for recurrent arrhythmia following ablation. Results: Average PIH fibrosis was 15.6 ± 5.8% of the left atrial (LA) volume. Depending on threshold (IIRthr ), the average IIR fibrosis (% of LA wall surface area) ranged from 5.0 ± 7.2% (IIRthr = 1.2) to 37.4 ± 10.9% (IIRthr = 0.97). An IIRthr of 1.03 demonstrated the greatest agreement between the methods, but spatial overlap of fibrotic areas delineated by the two methods was modest (Sorenson Dice coefficient: 0.49). Fourty‐two patients (41.2%) had recurrent arrhythmia. PIH fibrosis successfully predicted recurrence (HR 1.07; p = .02) over a follow‐up period of 362 ± 149 days; regardless of IIRthr, IIR fibrosis did not predict recurrence. Conclusions: PIH‐based volumetric assessment of atrial fibrosis was modestly predictive of arrhythmia recurrence following cryoballoon ablation in this cohort. IIR‐based fibrosis was not predictive of recurrence for any of the IIRthr values tested, and the overlap in designated areas of fibrosis between the PIH and IIR methods was modest. Caution must therefore be exercised when interpreting LA fibrosis from LGE‐MRI, since the values and spatial pattern are methodology‐dependent.